2019
DOI: 10.1186/s12882-018-1145-5
|View full text |Cite
|
Sign up to set email alerts
|

Asian Americans & chronic kidney disease in a nationally representative cohort

Abstract: BackgroundThere is a paucity of specific data on early stages of chronic kidney disease (CKD) among Asian Americans (AAs). The objective of this study was to examine the independent association of Asian race/ethnicity and socio-demographic and co-morbidity factors with markers of early kidney damage, ascertained by ACR levels, as well as kidney dysfunction, ascertained by eGFR levels in a large cross-sectional sample of AAs enrolled in the National Health and Nutrition Examination Survey (NHANES).MethodsSecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Previous studies showed that high lipotoxicity was engaged in the occurrence and development of diabetic nephropathy 21,3437. Other researches confirmed the significant calcium overload in diabetic nephropathy 3841. Moreover, calcium overload and lipid metabolites of PA provoked and upregulated calpain 10 which played an essential role in cell apoptosis 27,42.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies showed that high lipotoxicity was engaged in the occurrence and development of diabetic nephropathy 21,3437. Other researches confirmed the significant calcium overload in diabetic nephropathy 3841. Moreover, calcium overload and lipid metabolites of PA provoked and upregulated calpain 10 which played an essential role in cell apoptosis 27,42.…”
Section: Discussionmentioning
confidence: 93%
“…Calpain 10 regulates calcium ion efflux into the cytoplasm from mitochondria and endoplasmic reticulum, and triggers the apoptotic pathway 38. Studies show that Calpain 10-induced apoptosis in the cells of the superior renal duct aids in the development of DN.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies conducted on Asian and Caucasian populations have shown comparable odds ratios for eGFR < 45 mL/min/1.73 m 2 at 3.19 (1.99–5.1) for DM and 3.31 (2–5.48) for hypertension. Both variables were also significant risk factors for the decrease in eGFR to < 60 mL/min/1.73 m 2 25 . Since we only assessed the effects of BP targets on nondiabetic hypertensive patients, further large‐scale studies of both diabetic and nondiabetic hypertensive patients with different ethnic backgrounds must be conducted to validate these findings.…”
Section: Discussionmentioning
confidence: 97%
“…According to eGFR, CKD is divided into six categories by the international guideline group Kidney Disease Improving Global Outcomes (KDIGO) [11]: early CKD of stage 1 (eGFR of > 90 mL/min/1.73 m 2 ), stage 2 (eGFR of 60-89 mL/min/ 1.73 m 2 ), stages 3a (eGFR of 45-59 mL/min/1.73 m 2 ), and 3b (eGFR of 30-44 mL/min/1.73 m 2 ), late CKD stage 4 (eGFR of 15-29 mL/min/1.73 m 2 ), and stage 5 ESRD (eGFR < 15 mL/ min/1.73 m 2 ). In addition, eGFR is modified by age, sex, and ethnic group [12][13][14].…”
Section: Measures Of Chronic Kidney Diseasementioning
confidence: 99%